Subak Paddy Cluster System on Agricultural Sustainability in Bengkel Village, Kediri District, Tabanan Regency, Bali - Putri, Ravena Meisa; Mazwan, M. Zul (Jurnal Dinamika Sosial Ekonomi, 2025)
The Subak paddy cluster plays an important role in maintaining sustainable agricultural practices in Bali, especially in Bengkel Village, Kediri District, Tabanan Regency. The Subak system, as a world cultural heritage, not only manages water resources wisely but also reflects local wisdom that supports sustainability. The purpose of this research is to find out the subak paddy cluster system for the sustainability of n farming. This research was conducted in September 2023 in Bengkel Village, Kediri District, Tabanan Regency, Bali, using primary data collected through questionnaires and interviews with eight key informants who are active in the cluster. The method used was purposive sampling, analyzed using descriptive qualitative to understand the phenomenon in Bengkel Village. The results showed that the Subak paddy system cluster can increase paddy productivity to 7 tons per hectare from 5 tons per hectare through more efficient resource management and the application of modern technology. Socially, the existence of the cluster helps strengthen coordination among farmers, encourages closer cooperation, and improves community welfare through available institutional support. Economically, clusters have a positive impact by improving farmers' access to markets, creating more efficient distribution, and strengthening their ability to negotiate ppaddys. The implementation of environmentally friendly practices, such as the use of organic fertilizers, also supports the sustainability of the agricultural ecosystem. The development of innovation, both through product packaging and modern agricultural technology, is an important factor in improving competitiveness. By combining traditional and modern practices, agricultural clusters are able to create a more resilient and sustainable agricultural system.